Enhancement of colon carcinogenesis by the combination of indole-3 carbinol and synbiotics in hemin-fed rats - de Moura, Nelci A. [UNESP]; Caetano, Brunno F.R. [UNESP]; de Moraes, Leonardo N. [UNESP]; Carvalho, Robson F. [UNESP]; Rodrigues, Maria A.M. [UNESP]; Barbisan, Luis F. [UNESP] (Elsevier, 2018)
The risk of developing colorectal cancer (CRC) could be associated with red and processed meat intake. Experimental data supports that hemin iron, found abundantly in red meat, promotes CRC in mice and rats, while indole-3 carbinol (I3C) and synbiotics (syn) exert anti-carcinogenic activities in most studies of colon carcinogenesis. This study aimed to investigate the modifying effects of I3C and syn (inulin + Bifidobacterium lactis), given separately or together, on dimethylhidrazine (DMH)-induced colon carcinogenesis in hemin-fed rats. All animals were given four subcutaneous DMH injections and then, two weeks after carcinogen exposure, they began a basal diet containing hemin, hemin + I3C, hemin + syn, or hemin + I3C + syn for 23 weeks. The combination of I3C + syn significantly increased fecal water genotoxicity, tumor volume and invasiveness when compared to the hemin-fed control group. The groups fed I3C or syn alone had a significant reduction in the number of preneoplastic aberrant crypt foci (ACF) lesions compared to the hemin-fed group. Dietary I3C also reduced fecal water genotoxicity. Gene expression analysis of colorectal tumors demonstrated that the combination of dietary I3C + syn increased transcript levels for Raf1 and decreased tumor progression and invasiveness related to the genes Cdh1 and Appl1. This analysis also revealed that the Tnf and Cdh1 genes were significantly up- and down-regulated, respectively, in tumors of rats that received I3C, in comparison with the hemin-fed group. These findings reveal that the joint administration of I3C and syn enhanced the development of colon tumors induced by DMH in hemin-fed rats, while they potentially reduced ACF development when given alone.
Keywords: Chemoprevention; Colorectal cancer; Hemin; Indole 3-carbinol; Synbiotcs